2014
DOI: 10.5114/aoms.2014.47833
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis patients carrying G allele in –1082 G/A IL-10 polymorphism are predisposed to higher serum concentration of IL-10

Abstract: IntroductionAtopic dermatitis (AD) is a chronic skin inflammatory disease in which Th2-derived cytokines play an essential role. Aim of the study was to assess interleukin 4, 10 and 13 (IL-4, IL-10 and IL-13) serum concentrations in AD patients and to correlate the values with the occurrence of genotypes of selected polymorphisms in genes encoding these cytokines.Material and methodsSeventy-six AD patients (mean age 11.4 years) and 60 healthy controls were enrolled in the study. Blood samples were analyzed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…It is known that rs1800896 polymorphism, within the IL-10 gene promoter region, might influence IL-10 expression and plasma levels [37,38]. It was described that G-allele carrier patients have a better response to ALL treatment which includes glucocorticoids, leading to a better outcome [39,40] A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is known that rs1800896 polymorphism, within the IL-10 gene promoter region, might influence IL-10 expression and plasma levels [37,38]. It was described that G-allele carrier patients have a better response to ALL treatment which includes glucocorticoids, leading to a better outcome [39,40] A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Some of the studies in Caucasians found the IL-10 -1082G>A polymorphism not to be significantly associated with asthma [22,44], while others noted a protective effect on this disease [29] or a susceptible effect [45]. No difference in the prevalence of this polymorphism was found among atopic dermatitis subjects [42,43,46,47]. The IL-1α -889C>T polymorphism has not been significantly associated with asthma [22,40] and for atopic dermatitis there are studies demonstrating both no effect [14] and a susceptible effect [43].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding atopic rhinitis and dermatitis, the association of TNFα -308 polymorphisms has rarely been studied [14,41,42,43]. Additionally, there are only a few studies regarding other selected polymorphisms and atopic diseases, also with conflicting results [14,22,29,40,41,42,43,44,45,46,47]. Furthermore, confounding effects of lifestyle and environmental factors were rarely evaluated in studies assessing the association between genetic factors and atopic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Zhao carried out a meta-analysis of seven studies of the SNP that we found seemed to protect children against AD that considered a total of more than 800 AD subjects and about 1200 controls, 50 and found no direct association between IL10-rs 1800896 and susceptibility to, or the severity of AD, whereas Sohn et al 51 and Lesiak et al 52 have found close relationships between some IL10 promoter haplotypes and susceptibility to AD, and Lesiak et al have also found increased serum concentrations of IL10 in AD subjects with this SNP. 53 Moreover, Raedler et al found that carriers of three IL10 SNP blocks and distal promoter SNPs (including IL10-rs1800872) showed reduced levels of the expression of T reg cell markers, reduced IL-5, TNF-α and GM-CSF levels, and partially increased IFN-γ levels, and that the same SNPs were associated with the development of AD in 3-year-old children, 54 whereas Kijohara et al did not find any relationship between IL10 genetic variations and AD. 55 These conflicting findings may have been due to various factors, including differences in the ethnicity and general characteristics of the study populations, differences in the time of analysis and/or the assessment of clinical phenotypes, a failure to model gene/environment interactions adequately, 56 or the dual functional nature of IL10 itself.…”
Section: Discussionmentioning
confidence: 99%